New molecular mechanisms in castration-resistant prostate cancer - Virtanen, Verneri (fi=Turun yliopisto|en=University of Turku|, 2026)
Prostate cancer (PCa) is a major cause of cancer morbidity and mortality among men. Common therapy involves the reduction of circulating androgens to castrated levels. However, after the initial response, PCa eventually starts growing despite castrate levels of androgens, thereby becoming castration-resistant PCa (CRPC). There are no curative treatments for CRPC, and once PCa develops metastases, it becomes lethal. Therefore, elucidating the mechanisms of survival, growth, and metastasis in CRPC is necessary to develop improved therapies against CRPC. In this thesis, I have investigated new molecular mechanisms in CRPC, specifically, the interplay between androgen receptor (AR) signaling and BRCA1, the role of the BRCA1 protein in PCa, and metastasis formation regulation by the stress fiber contraction regulator caldesmon (CaD). We described AR-mediated activation of NRF2 via BRCA1 in CRPC by assaying PCa cell lines, murine xenografts, and patient samples. Moreover, this study showed that the dynamic regulation of BRCA1 by AR signaling may predispose to genetic alterations and promote castration resistance via enhanced reactive oxygen species defense. Additionally, we found that silencing CALD1 reduced metastasis in zebrafish PCa xenografts and spheroids in 3D culture. Our experimental and bioinformatic analyses suggest that CaD correlates with metastasis-associated epithelial-to mesenchymal transition in PCa. We discovered that antiandrogen resistance gives rise to cell populations expressing CaD and glucocorticoid receptor (GR), and found that GR upregulated CaD in PCa using a castration-resistant murine xenograft. Furthermore, we explored the potential for CaD as a drug target by characterizing a cald1 mutant zebrafish, which exhibited a non-lethal phenotype with a mild neural defect. This thesis demonstrated that different AR signaling states have the capacity to induce transient genomic instability and enhance defense against ROS via regulation of BRCA1 and BRCA1-mediated NRF2-activation. In this thesis, we have also identified the oncogenic properties of CaD as a mediator of PCa metastasis. Additionally, we found that cald1 mutations were tolerated and non-lethal in early zebrafish development, suggesting potential for CaD as a drug target.

Kastraatioresistentin eturauhassyövän uudet molekyylimekanismit Eturauhassyöpä aiheuttaa merkittävää sairastavuutta ja kuolleisuutta. Yleinen hoito perustuu miessukuhormonien laskemiselle kastraatiotasolle. Alkuvaiheen jälkeen eturauhassyöpä kuitenkin saa kyvyn kasvaa kastraatiotasosta huolimatta. Kastraatio resistenttiin eturauhassyöpään ei ole parantavia hoitoja. Etäpesäkkeitä kehittänyt tauti on kuolemaan johtava sairaus. Siksi on tärkeää selvittää tekijöitä, jotka mahdollistavat kastraatioresistentin syövän kasvun ja etäpesäkkeiden muodostumisen. Näiden mekanismien tunteminen on edellytys tehokkaampien hoitojen kehittämiselle. Tässä väitöskirjassa selvitin uusia molekyylimekanismeja kastraatioresistentissä eturauhassyövässä, erityisesti miessukuhormonireseptori-signaloinnin ja BRCA1:n vuorovaikutusta, BRCA1-proteiinin roolia eturauhassyövässä sekä caldesmonin (CaD) roolia etäpesäkkeiden muodostumisessa. Osoitimme miessukuhormonin aktivoivan NRF2:a BRCA1-välitteisesti hyödyntämällä solumalleja, hiiri-xenografteja ja potilasnäytteitä. Tutkimuksemme osoitti, että BRCA1:n dynaaminen säätely eturauhassyövässä voi altistaa geneettisille muutoksille ja edistää kastraatio resistenssiä antioksidanttipuolustuksen kautta. CALD1:n hiljentäminen eturauhassyöpäsoluissa vähensi niiden kykyä muodostaa etäpesäkkeitä seeprakala-xenografteissa sekä pienoiskasvaimia 3D-ympäristössä. Havaitsimme, että CaD osallistuu säätelemään muutosta epiteelisoluista mesenkymaalisoluiksi. Havaitsimme kastraatioresistentteissä hiiri-xenografteissa solupopulaatioita, jotka ilmensivät sekä CaD:a että glukokortikoidireseptoria (GR). Lisäksi osoitimme, että GR säätelee CaD:n ilmentymistä eturauhassyövässä. Kuvailimme myös cald1-mutaatioiden vaikutukset seeprakalassa. Mutanttien fenotyyppi ei ollut letaali ja ilmentyi korkeintaan lievänä hermoston kehityshäiriönä. Tässä väitöskirjassa tunnistettiin, että erilaiset miessukuhormoni-signaloinnin tilat voivat aiheuttaa ohimenevää geneettistä epävakautta ja vahvistaa antioksidanttipuolustusta BRCA1:n ja NRF2-aktivoinnin kautta. Lisäksi väitöskirja osoitti CaD:n aiheuttavan etäpesäkkeitä eturauhassyövässä ja että seeprakalat sietävät hyvin cald1-mutaatioita varhaisessa kehityksessä, mikä viittaa CaD:n olevan mahdollinen lääkekohde.